Bringing home the bacon! A contrastive study of the cognates bring/bringe in English and Norwegian - Oksefjell Ebeling, Signe (Kalbotyra, 2017)
This paper highlights the value of a bidirectional translation corpus in contrastive studies in an investigation of the cross-linguistic relationship between two cognates in English and Norwegian: bring and bringe. Although monolingual and bilingual dictionaries prove to be excellent sources of information in respect of this relationship, the present study contributes further to our knowledge regarding the cognates’ conditions of use. Drawing on material from the fiction part of the English-Norwegian Parallel Corpus (ENPC), the study reveals that English bring is far more frequent than its Norwegian counterpart. By exploring the close to 500 occurrences of the two words in original and translated texts, it becomes clear that the two verbs have a relatively low Mutual Correspondence. That is, overall, they only correspond to each other in translation in roughly 20% of the cases. This low correspondence rate is surprising, given the fact that we are looking at verbs stemming from the same origin in two closely related languages. The corpus correspondences suggest that there may be at least two main reasons for this. First, Norwegian bringe may be considered more formal than English bring and there is thus a preference for using less formal verbs in Norwegian to express the meaning of bring, notably the multi-word verbs ha med (REFL) ‘have with (REFL)’, ta med (REFL) ‘take with (REFL)’ and komme med ‘come with’. Second, English bring is more versatile than Norwegian bringe, particularly in the sense that it more readily forms part of phrasal verbs and fixed phrases. It is also the case that English bring has come to be used with a wider range of meanings than Norwegian bringe, as attested in the dictionaries consulted. These ‘extra’ meanings include ‘initiate legal action against someone’ and ‘force oneself to do something (unpleasant)’; however, neither of these meanings is particularly salient in the current data. The findings underline the role a parallel corpus such as the ENPC can play in shedding light on contrastive nuances that contribute to a broader understanding of cross-linguistic relationships.